BAJAPUIK DALAM TRADISI PERKAWINAN DI KOTA PARIAMAN - Renanda Putri; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bajapuik in Marriage Tradition in Pariaman. This research was conducted in the city of Pariaman. The purpose of this study was to determine how the Bajapuik marriage procession in the community in Kota Pariaman, and to find out the meaning and function of Bajapuik marriage. In determining research subjects using purposive sampling technique, which is predetermined based on criteria. This study uses qualitative research methods with data collection techniques by conducting interviews and documentation. The number of informants in this study amounted to 9 people. The theory used is Malinowski's theory of functionalism and Mead's theory of meaning (symbolic interactionism). The result of this research is that the Bajapuik marriage tradition is a marriage custom by using pick-up money in the Minangkabau tribe which is included in the customary level. Adat nan dikadatan or Adat dikadasikan is a local rule that is taken by using the word consensus or custom that is generally accepted in a village or area. In the Bajapuik custom, a man is one step elevated from a woman, this is illustrated by the procession of proposing or proposing by the woman, where the man in the Bajapuik tradition is picked up and married by the woman and uses the japuik money as a pick-up for the man. -that man. Bajapuik has a function to help each other. This tradition is useful and beneficial for the closeness between families who carry out the marriage process using the Bajapuik tradition, and has the meaning of mutual respect for both parties involved. Keywords: Tradition, Bajapuik Marriage